2017
DOI: 10.1111/nep.12778
|View full text |Cite
|
Sign up to set email alerts
|

Simple renal cysts in the solitary kidney: Are they innocent in adult patients?

Abstract: Simple renal cysts in solitary kidney patients with impaired renal function is associated with poor renal outcome. Large-scale studies are needed to clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…The conclusion was that the relative renal function of the cystic kidney was lower than that of the contralateral kidney (p = 0.001). Another recent study further verified whether cysts with moderate renal dysfunction were associated with poor renal result in patients with a solitary kidney [19] . On the contrary, Rule et al [8] found renal cysts to be associated with increased GFR (hyperfiltration) in the potential donor population.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion was that the relative renal function of the cystic kidney was lower than that of the contralateral kidney (p = 0.001). Another recent study further verified whether cysts with moderate renal dysfunction were associated with poor renal result in patients with a solitary kidney [19] . On the contrary, Rule et al [8] found renal cysts to be associated with increased GFR (hyperfiltration) in the potential donor population.…”
Section: Discussionmentioning
confidence: 99%
“…Tatar et al. 23 reported that SRCs are associated with poor renal function outcomes in solitary kidney patients. In Korea, Choi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The association of membranoproliferative glomerulonephritis (MPGN) with solid tumour remains rare. [1][2][3][4][5][6][7] MPGN is more typical of lymphoproliferative disorders. 8 A 65-year-old gentleman, hypertensive for 5 years, presented with a history of pedal oedema, facial puffiness and breathlessness for 20 days duration.…”
Section: Venkateswara Institute Of Medical Sciences Nephrologymentioning
confidence: 99%
“…We read the interesting paper recently published by Tatar et al in Nephrology . In a cohort of 65 adult patients who underwent nephrectomy for oncological and non‐oncological causes, simple renal cyst was present in 30% of patients.…”
mentioning
confidence: 99%